Radiation dose to Malaysian populace via the consumption of roasted ground and instant coffee. (August 2020) - Khandaker, Mayeen Uddin; Zainuddin, Nur Khairunnisa; Bradley, D.A.; Faruque, M.R.I.; Almasoud, F.I.; Sayyed, M.I.; Sulieman, A.; Jojo, P.J.
Abstract: Accompanying the busy lifestyles of modern Malaysia, coffee is becoming one of the nations' most popular stimulating drinks. In association with nutrients uptake, natural radionuclides in soil are also being taken up by the coffee plant, subsequently appearing in the human body through consumption of coffee. Present study concerns the assessment of the natural radionuclides 226 Ra, 228 Ra, and 40 K in roasted ground and instant coffee consumed in Malaysia. A total of 12 sampled brands of coffee, originating from seven different countries including Malaysia, were collected from various supermarkets in Kuala Lumpur. The samples were analyzed by HPGe γ-ray spectrometry, obtaining a range of activities (in Bq/kg) 6.4 ± 1.3–21.4 ± 2.4, 6.6 ± 1.8–47.9 ± 10.6, and 220 ± 12–1510 ± 72 for 226 Ra, 228 Ra and 40 K respectively. The annual committed effective dose estimate from such coffee consumption was found to be in the range 13.2–55.7 μSv/y, low in comparison with the UNSCEAR (2000) reference dose guidance limit of 290 μSv/y. The estimated threshold coffee consumption rates indicates a guidance limitation for Sample L of not more than 21 g/d (some 2 cups/d) to avoid deleterious health effect. While the presently sampled coffee brands do not represent a public concern in terms of radiological risk, cumulative daily dietary exposures from other or present brands may not be totally negligible because of the UNSCEAR reference limit is due to the contribution from all natural sources. Thus, periodic monitoring of radiation levels in coffee is suggested to be of importance. Highlights: Information on the distribution and enrichment of radionuclides in coffee found to be sparse. Addressed in investigating 12 popular brands of coffee from seven countries, assessed for U-, Ra- and K- content. Committed effective dose from their consumption low compared to UNSCEAR guidance limit of 290 μSv/y.